Sociodemographic determinants of internet use and its impact on family planning behavior among young male in Ethiopia: evidence from EDHS 2016 - Yesuf, Kedir Abdu (International Journal of Scientific Reports, 2021)
Background: Internet was preferred source of health information to retrieve relevant information. The study investigated sociodemographic determinants of internet and its impact on family planning behavior among young male in Ethiopia, 2016. Methods: The study was based on data from Ethiopia health and demographic survey 2016. The sample size was 4550 male youth age between 15-24 years include in EDHS 2016. Multilevel logistic regression was used to determine sociodemographic factor associated with internet utilization. The impact of internet use on family planning behaviors was assessed by propensity score matching using average treatment effect. Results: The magnitude of internet use in Ethiopia was 14% and factor associated with internet use included age between 20-24 years (AOR=0.60; CI=0.46-0.79), urban resident (AOR=3.94; CI=2.75-5.64), higher educational level (AOR=12.98; CI=2.69-62.66), lived in city administrative region (AOR=2.18; CI=1.46-3.28), respondent own mobile phone (AOR=8.00; CI=95.58-11.48), respondent who able to read whole sentence (AOR=4.04; CI=2.54-6.44) and respondent who has computer in household (AOR=2.03, CI=1.22-3.40) more likely to use internet. In other hand respondent occupation of agricultural and manual has 56% (AOR=0.44; CI=0.3-0.61) and 46% (AOR=54, CI=0.36-0.81) less likely to use internet. The average treatment impact of internet use on exposure to internet about FP, male condom uses and knowledge about FP increase by 12%, 7.2% and 4.5% percent point respectively. Conclusions: In spite of fast-growing nature of internet and popularity among youth people. In the future, integrating health information to different platforms on the internet will be a most effective way of health promotion.